What can TOLs reveal about the nature of ESL reading? : a critical evaluation of current ESL research utilising think-aloud protocols - Dixon, Robyn (Rhodes University, Faculty of Education, Department of Education, 1993)
This thesis explores the efficacy of think-aloud protocols (TOLs), and the extent to which the TOL technique is able to reveal the nature of ESL reading interaction with expository prose. The investigation constituted a critical evaluation of current ESL TOL research, which was essentially a theoretical examination of emerging problems derived from an in-depth assessment of current ESL TOL studies. The theoretical examination was supplemented by the practical implementation of the technique in a case study research, utilising three verbal protocols obtained from ESL students at the University of Fort Hare. The close observation afforded by the evaluative case study research paradigm provided the writer - as participant observer - with a further means of judging the merit of TOLs, which corroborated findings from the theoretical evaluation, and enabled a consideration of unanticipated issues which emerged from the practical implementation of the technique. The conclusion was that TOLs seem to have a unique ability to identify aspects of the nature of ESL reading gained from an on-line assessment of reader interaction, provided that TOL research is conducted within certain methodological and analytic research constraints. The writer has proffered suggestions for future ESL TOL research, and feels that the combination of TOL research findings with other measures of reading comprehension could elucidate aspects of ESL comprehension, making a valuable contribution to ESL reading theory and practice.
Keywords: English language -- Study and teaching -- Foreign speakers; Reading comprehension Reading -- Research